2002
DOI: 10.1086/324354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Discontinuation of Initial Protease Inhibitor Therapy on Further Virological Response in a Cohort of Human Immunodeficiency Virus–Infected Patients

Abstract: Although discontinuation of antiretroviral drug therapy is common, the impact on outcome in routine clinical practice is unknown. The Antiprotéases Cohorte (APROCO) Cohort Study enrolled 1281 patients at the time they started a protease inhibitor (PI)-containing regimen from 1997 through 1999. After a median duration of follow-up of 20 months, 51% of patients had discontinued their initial PI. Prospectively recorded reasons for discontinuation were intolerance (52% of patients), poor adherence (22%), and failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…1,7,[9][10][11][12][13][14] The most frequently reported side effects are gastrointestinal, including nausea, vomiting, and diarrhea. The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,7,[9][10][11][12][13][14] The most frequently reported side effects are gastrointestinal, including nausea, vomiting, and diarrhea. The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…23 Psychosocial factors, such as the position of many women as the primary caregiver for others, are other possible differences that could lead to higher rates of discontinuation in females. 13,21,[23][24][25] These findings highlight the need for further investigation regarding the pharmacokinetic differences and psychosocial factors leading females to be more likely to discontinue HAART regimens so that effective interventions may be developed.…”
Section: Robison Et Al 1352mentioning
confidence: 99%
See 1 more Smart Citation
“…Xavier Duval, 1 Valé rie Journot, 2 Catherine Leport, 1 Geneviè ve Chê ne, 2 Michel Dupon, 3 Lise Cuzin, 5 Thierry May, 6 Philippe Morlat, 4 Anne Waldner, 7,a Roger Salamon, 2 Franç ois Raffi, 8 HAART has led to a substantial decrease in morbidity and mortality and has become the standard-of-care for treatment of HIV infection [1]. Eradication of HIV is currently elusive with available therapy; because interruption of treatment leads to the resumption of viral replication, HAART needs to be continued indefinitely for clinical and immunovirological benefit to be pre-served.…”
Section: Incidence Of and Risk Factors For Adverse Drug Reactions In mentioning
confidence: 99%
“…Additionally, antiretroviral (ARV) medications, particularly the protease inhibitor (PI) class, have been recognized as frequent causes of GI complaints leading to ARV discontinuation. 7-9 …”
Section: Introductionmentioning
confidence: 99%